Assessment of Wave Attenuation Performance of the Tanjung Piai Breakwater Using Spectral Wave Analysis - Sofian Tan, Iwan Tan; Teh, Hee Min; Nik Hassan, Nik Mohd. Kamel (International Journal of Integrated Engineering, 2023)
Tanjung Piai is one of Malaysian heritage sites situated at the southernmost tip of the Asian continent. Tanjung Piai provides a conducive coastal habitat for many mangrove species, including the rare species of Bruguiera hainesii and Bruguiera sexangula. Coastal erosion resulting in shoreline retreat that was detected dating back to the 1930s. Due to uncontrolled coastal development ij the vicinity of Tanjung Piai, the erosion rate at the mangrove site had accelerated since the recent decades. This led to significant land mass loss that threatens the eco-system. Various measures have been undertaken to mitigate the erosion problems. Some measures were adopted to permanently harden the shoreline preventing sea water from reaching the mangroves. However, this resulted in mangroves gradually dying along the coast.. A series of offshore breakwaters were subsequently planned to reduce wave energy, mitigate the erosion and protect the existing mangroves growing along the wave-exposed coastline. This study aims to assess the impact of offshore waves, squalls and wind-generated waves to the Tanjung Piai coastline (with and without the breakwaters) using a two-dimensional numerical model. A survey of the site and details of the breakwaters’ design were incorporated in the modelling. The numerical results show that the breakwaters are able to reduce offshore wave heights up to 66%. The breakwaters can attenuate offshore waves more effectively compared to squalls and wind-generated waves. The breakwaters were completed in 2019. They were proven to be able to provide protection to the mangroves along the coast of Tanjung Piai